The Relationship between Self-Efficacy and Family Support, Adherence to Taking Hypertension Medication - Abdul Hadi; Parellangi; Amirudin (Asian Journal of Healthcare Analytics, 2023)
Hypertension Is a condition where the increase in systolic blood is above the normal limit, which is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg (WHO, 2021). Hypertension or high blood pressure is often referred to as "the silent killer" because it is often without complaints. To determine the relationship between self-efficacy and family support with adherence to taking hypertension medication in the Working Area of ​​the Tubaan Health Center, Berau Regency. The design of this study was a descriptive correlation with a cross-sectional approach which was carried out in February-March 2022. The population in this study were hypertension sufferers in the working area of ​​the Tuban Health Center, Berau Regency, totaling 120 people. Determination of the sample using purposive sampling, then obtained a sample of 54 respondents. The statistical test used is Chi Square if t count (pvalue) <0.05 is obtained, then the hypothesis Ha is accepted and Ho is rejected. Shows that respondents with good self-efficacy are 39 people (72.2%), have good family support both 18 people (33.3%), and respondents who adhered to taking medication amounted to 36 people (66.7%). The results of the analysis using the chi-square test obtained a p-value = 0.028 <0.05 & a p-value = 0.001 <0.05, which means that Ho 1, Ho 2 are rejected and Ha 1, Ha 2 are accepted. There is a relationship between self-efficacy and family support with adherence to taking hypertension medication in the working area of ​​the Tubaan Health Center, Berau District.